Lung carcinoma paraneoplastic reactive regional pericarditis mimicking ST elevation myocardial infarct. Issue 6 (2nd November 2021) - Bijay, Yadav; Miriyala, Varun; Pant, Sadip; Chander, Ravi; Nosheen, Javed; Turcotte, Keith D.; Rizk, Sophia; Mucciardi, Nick; Randy, Kaplan; Cao, Shanjin
ABSTRACT: ST-elevation myocardial infarction (STEMI) is a cardiac emergency. However, multiple clinical disorders can cause ST-elevation ECG changes, one of which is pericarditis. Regional pericarditis is a less known clinical phenomenon that can mimic STEMI. We report a case of poorly differentiated lung carcinoma associated reactive regional pericarditis mimicking inferior STEMI.